Effectiveness of Handling Complaints and Community Satisfaction in Population Administration Services in Malang City - RAHMA BAITS NUR, AYU WANDANI MUSTIKA (PANGRIPTA, 2025)
The Malang City Government continues to strive to improve the quality of population administration services, especially in the effectiveness of the complaints system in Malang City Population and Civil Registration Service (Dispendukcapil).. Service standards set out in Decree of the Head of the Malang City Population and Civil Registration Department Number 188.451/66/35.73.409/2024 emphasizes transparency, accountability and responsiveness in handling public complaints. However, the effectiveness of the complaint system is still a challenge, especially in terms of speed of response, ease of access, and compliance with service standards. This research aims to measure the influence of the effectiveness of the complaints system on the level of community satisfaction in population administration services in Malang City. The method used is quantitative with approach survey towards the service user community. Data were analyzed using linear regression to test the relationship between complaint effectiveness variables and community satisfaction. The research results show that the effectiveness of the complaint system has a significant influence on community satisfaction. Factors such as response speed, information transparency, And easy access to complaint services contribute to increasing service user satisfaction. However, several obstacles are still found, such as lack of socialization of complaint mechanisms And variability in the speed with which complaints are handled. These findings emphasize the importance of increasing the effectiveness of the complaints system through optimization of digital mechanisms, improving HR skills, as well as continuous evaluation of service standards, to ensure better quality of service for the people of Malang City.